2023
DOI: 10.1680/jstbu.20.00305
|View full text |Cite
|
Sign up to set email alerts
|

Numerical study of reliability index of structure rehabilitated with steel shear wall

Abstract: Uncertainties in seismic demand and structural capacity create conservatism in the acceptance criteria of structural performance levels. This conservatism can be reduced and designs optimised by considering and reducing uncertainties. In seismic rehabilitation, a secondary system added to an existing structure has probabilistic parameters that can lead to changes in existing uncertainties. In this work, a steel moment frame was rehabilitated with a steel shear wall (SSW). Structural uncertainties were investig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 32 publications
0
0
0
Order By: Relevance
“…Ghassemieh and Bamshad [36] studied and compared the energy dissipation of one-story SPSWs using finite element modelling. Maddahi et al [37] studied the reliability index of rehabilitated structures with SPSWs and the obtained results showed that the rehabilitation of the damaged walls using steel web plates could improve their structural performance.…”
Section: Introductionmentioning
confidence: 99%
“…Ghassemieh and Bamshad [36] studied and compared the energy dissipation of one-story SPSWs using finite element modelling. Maddahi et al [37] studied the reliability index of rehabilitated structures with SPSWs and the obtained results showed that the rehabilitation of the damaged walls using steel web plates could improve their structural performance.…”
Section: Introductionmentioning
confidence: 99%